WHY TRADITIONAL MARKET BUYERS GOING DIGITAL: An Empirical Study on Switching Behavior - Wiyata (Journal Publicuho, 2023)
This study attempts to provide a strengthened understanding of why people switch from traditional payment to digital payment QRIS (Quick Response Code Indonesian Standard). Grounding on the push, pull, mooring model as framework, I proposed dissatisfaction and transaction incovenience as the push factor, easy of use and critical mass as the pull factor, and switching cost as the mooring factor. I tested the proposed model by conducting a paper-based survey in Surakarta’s traditional market at Center of Java, Indonesia by comprising respondents comprising a total of 150 buyers. The results of PLS-SEM analysis demonstrated that except transaction inconvinience, all the proposed variables have been confirmed. From a theoretical implication, this study offers significant contributions to switching behavior literature by invesitivigating the applicability of the PPM Model in tradiotional market context. From a practical implication, these findings provide useful implications and insights for digital payment brands on how to encourage costumers switching from their traditional payment habits.